Muslim Consumer Behavior Towards Halal Industry 4.0: Attitudes And Perceived Risk - Anifatul Hanim; Ivana Rosediana Dewi; Nanik Istiyani (UNEJ e-Proceeding, 2021)
The development of industry 4.0 today requires the entire business industry to adapt to changes in technology and science, including the halal industry, namely by digitizing the halal industry and Muslim consumers. It is necessary to study how Muslim behavior in the decision to purchase a halal product in order to optimize the halal industry. Muslim consumers implement Islamic values and principles in consumption behavior so that they have different characteristics from consumer behavior in conventional theory. Muslim consumers are influenced by internal and external factors in making purchasing decisions for halal products, including subjective norms, perceived behavioral control, self-identity, halal awareness, religiosity, purchasing decision strategies, online consumer behavior consisting of perceived risk, technology acceptance. and online trusts. The purpose of reviewing the theory of Muslim consumer behavior is to be able to optimize the development of the halal industry by recognizing the behavior of Muslim consumers as the target market for the Muslim industry so that they can compete and develop halal products according to the needs and demands of Muslim consumers in the industrial era 4.0. Keywords: Industry 4.0, Halal Industry, Muslim Consumer Behavior, Purchasing Decisions